Adoption of Sassakawa Global 2000 Maize Production Practices: A case study of Yelwa Area of Bauchi Local Government Area of Bauchi State, Nigeria - Oluwole, Adeosun, J.; Dutse, Nanyi J.; Titus, J. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
A study was carried out in November, 2014 to determine the adoption of Sassakawa Global 2000 Maize production practices in Yelwa Area of Bauchi local Government Area of Bauchi state. Two hundred (200) questionnaires were proportionately distributed among the six (6) villages in Yelwa Area, namely Yelwa Lebura/Tudu, Birshi-Fulani, Lushi, Sabon Kaura, Gwallameji and Kagadama. One hundred and ninety two questionnaires were filled and returned and were analyzed using simple frequency and percentages. The study revealed among others that most farmers in the study area that adopted the technology were in their active and productive ages and some of them had one form of education or the other which enhanced them to adopt and practiced the technology a bit easier. It is also an indication that maize production has a promising future in the study area. Extension agents contributed meaningfully towards the success recorded in Sassakawa Global 2000 in the study area not only by taking the innovation to the farmers but also in linking them up to source of good seed. Overall result indicated a good percentage yield increase as a result of adoption of SG 2000 compared to the existing traditional method of maize production in the study area. It is therefore recommended among other things that more training, workshop and meeting should be organized by relevant bodies like Agricultural Development Programme for the farmers in the study area and the state as a whole to enlighten farmers on the true application of the agronomic principles of Sasakawa technology such as early planting, incorporation of fertilizer into the soil, early weeding, disease/pest control, proper spacing and correct plant population. Land acquisition should be made easy for people who want to engage in farming. Farm inputs should be provided at affordable prices for the farmers.